PERANCANGAN SISTEM INFORMASI MANAJEMEN RESTORAN PADA KEDAI IN AJA - Rangga Dimas Permadi; Anis Mirza (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Kedai in Aja is a restaurant that is growing rapidly. However, along with the increasing number of Covid 19 cases that require business owners to implement health protocols, restaurant owners want their place of business to apply health protocols to the maximum so that customer trust in their restaurants is maintained properly. Therefore, a restaurant management information system was built that has a direct food ordering feature through the smartphone of each customer, in the hope of reducing physical contact between customers and restaurant staff, as well as improving order documentation so that it can be accessed by restaurant owners anytime and anywhere. The result of making a restaurant management system application for Kedai in Aja is that customers can place orders independently through their respective smartphones. Ordering includes menu selection, table selection, and selection of payment methods. Every order that comes in is documented and can be accessed directly by the restaurant owner anytime and anywhere while having an internet connection.